Dancing to the Rhythms of the Fossil Fuel Landscape: Landscape Inertia and the Temporal Limits to Market‐Based Climate Policy. Issue 1 (14th July 2016) - Carton, Wim
Abstract: This article makes a contribution to the critique of market‐based mechanisms for climate and energy policy. It explores the environmental effectiveness of market instruments by engaging a broadly conceived "fossil fuel landscape", or the material, social, and political inertia of fossil energy dependence, as a factor delimiting policy outcomes. The argument is developed through a focus on the idea of economic efficiency as a key ideological construct underlying market‐based policy, and draws on examples from two different market instruments, namely the EU Emissions Trading Scheme, and the Flemish tradable green certificate scheme. I argue that an understanding of the shortcomings of these, and similar, policies requires acknowledgment of the political and socio‐economic power that emanates from the temporal dynamics of fossil fuel capitalism, which are reproduced when economic efficiency becomes the key focus of climate policy.